IMPLEMENTASI ASSESSMENT FOR LEARNING BERBASIS GAMIFIKASI DALAM UPAYA MENINGKATKAN HASIL BELAJAR MURID SMP - Cindy Kharisma Dewi; Wahyu Budi Sabtiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning outcomes are caused by suboptimal assessment practices that are not integrated into the learning process, resulting in a lack of meaningful feedback. This study aims to examine the improvement of student learning outcomes through the implementation of assessment for learning based on gamification in the topic of ecosystem component interactions. The study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The participants were 30 seventh-grade students of SMP Negeri 5 Surabaya. Data were collected through tests, observations, and questionnaires, and analyzed using the Shapiro–Wilk test, Wilcoxon test, and N-gain calculation. The results showed that the average pretest score of 52.0 increased to 84.3 in the posttest, with an N-gain value of 0.68 categorized as moderate, and the Wilcoxon test indicated p < 0.001, showing a significant difference. The implementation of learning based on TGT syntax and assessment for learning characteristics was categorized as very good and improved in the second meeting, while student activities showed improvement in motivation, engagement, and response during learning. Student responses were also categorized as very good, ranging from 88.3% to 97.5%. These findings indicate that gamification-based assessment for learning can improve student learning outcomes, engagement, and the quality of the learning process.